Competitive Gold‐Activation Modes in Terminal Alkynes: An Experimental and Mechanistic Study. Issue 3 (6th December 2013) - Gimeno, Ana; Cuenca, Ana B.; Suárez‐Pantiga, Samuel; de Arellano, Carmen Ramírez; Medio‐Simón, Mercedes; Asensio, Gregorio
Abstract The competition between π‐ and dual σ, π‐gold‐activation modes is revealed in the gold(I)‐catalyzed heterocyclization of 1‐(o‐ethynylaryl)urea. A noticeable effect of various ligands in gold complexes on the choice of these activation modes is described. The cationic [Au(IPr)]+ (IPr=2, 6‐bis(diisopropylphenyl)imidazol‐2‐ylidene) complex cleanly promotes the π activation of terminal alkynes, whereas [Au(PtBu3)]+ favors intermediate σ, π species. In this experimental and mechanistic study, which includes kinetic and cross‐over experiments, several σ‐gold, σ, π‐gold, and other gold polynuclear reaction intermediates have been isolated and identified by NMR spectroscopy, X‐ray diffraction, or MALDI spectrometry. The ligand control in the simultaneous or alternative π‐ and σ, π‐activation modes is also supported by deuterium‐labeling experiments.